Людинознавчий підхід до навчання (автодидактичний аспект) - Старко, Феодосій Васильович; Starko, Feodosii V. (Волинський національний університет імені Лесі Українки, 2009)
В статті висвітлено людинознавчий підхід до навчання. Українська постпсихологічна автодидактика знайомить із унікальною та всесвітньовідомою методикою самонавчання, яку застосовують сьогодні люди різноманітних професій та покликань у безлічі галузей. The article considers the contemporary tasks faced by Ukraine’s education system and trends in searching for new pedagogical technologies that would help education institution address the foremost problem — developing thinking, an ability to analyze the situation and plan one’s actions in advance, to adequately assess the results, independently acquire and process information (turning knowledge into a tool to learn other types of activities), as well as an ability to interact with others in a constructive way, i. e., the task of shaping the intellectual culture of an individual.
Humanological Approach to Teaching (Autodidactic Aspect)
Роботу виконано на кафедрі теорії та методики природничо-математичних дисциплін початкової освіти
Keywords: автодидактика; внутрішній світ; метод; мислення; інтерес; знання; method; inner world; thinking; interest; autodidactics; knowledge